IbM OTAK-OTAK BANDENG KHAS SURABAYA DESA CARIKAN KELURAHAN ALON-ALON CONTONG, KECAMATAN BUBUTAN SURABAYA - Siti Mundari; Zainal Arief; Erm Yuliaty (JPM17: Jurnal Pengabdian Masyarakat, 2016)
Otak-otak Bandeng is one of a traditional food from Surabaya that likedby own Surabaya people and outside Surabaya.Consider with its one of SmallMedium Entrepreuner (UKM) still produce “ Otak-otak Bandeng “ till recentlyare the Carian Villagers, house or off led by Mrs.Fatimah (First Patner). TheseUKM of Mrs. Fatimah contains 12 people that from womens surroundingsespecially housewife,most of them unlucky family. Actually these womens UKMhad been long time and still continue now. The produck has been distributed tomany near market,some offices,more customer buy as souvenir traditional foodfrom Surabaya. The problem of UKM is over demand capacity but unable tofulfilled caused by product capacity limit and over time product process(maximum 10 kilos made 30 pieces otak-otak Bandeng for 9 hours each day),except its also the product cant stay long causes product condition after gotsteam still contains dig water incase the product should have keep for nighttodried first then fried to distributed. However ,when distributed the productwould early expired so can caused distributed range unwide. Beside productioncapacity problem, these UKM doesn’t understood how to managed finance sotheres no specific account for cost of goods production value neither accountingdebt credit. In that case IbM Team help must excepted to increase productioncapacity and couting about finance management so they could increasedincome of Carian womens villager house or off Alun-alun Contong Sub DistrictBubutan that most of them under prosperity.Key words : Otak-otak Bandeng, production capacity